AN ANALYSIS OF STUDENTS’ COMMON ERROR IN WRITING DESCRIPTIVE TEXT AT THE 2ND GRADE OF MA NURUL HUDA SUNGAI LUAR - Ardian Supianda; Samsul Amri (Program Studi Pendidikan Bahasa Inggris Fakultas Keguruan dan Ilmu Pendidikan, 2018)
The goal of this research was to find out the students’ common error in writing descriptive text at the 2nd grade of MA Nurul Huda Sungai Luar. This research belongs to descriptive study, specifically descriptive qualitative. In order to find out the students’ common error, the researcher used a written text where the students should write their own descriptive text. Students’ writing were assessed based on global error which consist of error in verb tense (vt), word order (wo), connector (conn), local error which can be divided into article error (art), number (num), and organization error (identification error and description error). After collecting the data, the researcher analyzed them by describing the errors. As the result, the researcher found that the students made 143 errors which can be separated into verb tense is about 73 or 51%, word order 14 or 10%, connector 7 or 5%, article 8 or 5,5%, number 26 or 18%, and identification 15 or 10,5%. At the end, since the goal of this research is to find out the common error, it can be concluded that the common one is error in using verb tense (vt).